The clinical efficacy of ozone combined with steroid in the treatment of discogenic low back pain: a randomized, double-blinded clinical study - Yang, Xiao-hui; Liu, Xiao-hui; Ma, Yun-gai; Fan, Jia-xing; Ma, Xiao-long; Zhuang, Guan-ying; Yang, Zhan-min (Frontiers in Neurology, 2023)
Objective This randomized double-blinded clinical study is to investigate the clinical efficacy of per-paravertebral disk ozone injection combined with steroids in the treatment of patients with chronic discogenic low back pain (CDLBP). Methods Group A (N = 60) received a per-paravertebral injection of a steroid mixture of 10 mL with pure oxygen 20 mL, while group B (N = 60) received a per-paravertebral injection of a steroid mixture of 10 mL combined with ozone 20 mL (30 μg/mL). Injections were administered once a week for 3 weeks, with a follow-up of 6 months. Clinical outcomes were assessed at week 1, month 3, and month 6 with the help of Visual Analog Scale (VAS) scores and Macnab efficacy evaluation. Results The VAS score of both group A (1.65 vs. 6.87, p = 0.000) and group B (1.25 vs. 6.85, p = 0.000) at week 1 was significantly reduced compared to baseline. The effect was sustained at the 3- and 6-month follow-up periods (p < 0.05). Group B had significantly lower VAS scores at month 3 (1.53 vs. 3.82, p = 0.000) and month 6 (2.80 vs. 5.05, p = 0.000) compared to group A, respectively. Based on Macnab criteria, 95 and 96.7% of patients in groups A and B had good rates “excellent plus good” at week 1, respectively. Good rates were significantly higher in group B at month 3 (91.7 vs. 78.3%, p = 0.041) and month 6 (85.0 vs. 68.3%, p = 0.031) compared to group A, respectively. No serious adverse events were noted in both groups. Conclusion Per-paravertebral injection of steroid and ozone combination resulted in better relief of CDLBP compared to pure oxygen plus steroid. Clinical Trial Registration ChiCTR2100044434 https://www.chictr.org.cn/showproj.html?proj=121571.